Authors of the “Daurian Versailles” in Nerchinsk - Kradin, Nikolai (project baikal, 2022)
The article presents the biographical information about the creative work in Transbaikalia of the architect V. I. Kulikovsky and his wife, sculptor E. S. Kulikovskaya, co-authors of the famous Butins Palace in Nerchinsk, popularly called “Daurian Versailles”. The author analyzes stylistic, compositional and planning features of different types of buildings in the palace complex, as well as in Nerchinsk and at the Butins’ dacha in Nizhniy Stan. The author also describes the architect Lavrenty Ivanov’s works, who was the author of the Gostiny Dvor in Nerchinsk.